2014
DOI: 10.1021/nn5023632
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy of Optical Transitions and Vibrational Energies of ∼1 nm HgTe Extreme Nanowires within Single Walled Carbon Nanotubes

Abstract: This paper presents a Resonance Raman spectroscopy study of ~1 nm diameter HgTe nanowires formed inside single walled carbon nanotubes by melt infiltration. Raman spectra have been measured for ensembles of bundled filled tubes, produced using tubes from two separate sources, for excitation photon energies in the ranges 3.39 to 2.61eV and 1.82 to 1.26eV for Raman shifts down to ~25 cm -1 . We also present HRTEM characterization of the tubes and the results of DFT calculations of the phonon and electronic dispe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 49 publications
0
48
0
Order By: Relevance
“…15 The samples were then fully characterised using HRTEM to ensure that no extraneous HgTe remained and determine the atomic structure of the filling structures. 15,16 Inspection of more than 100 SWCNTs from the supplied sample by HRTEM revealed that the significant majority (~85%) fall within a limited diameter range of 1.2-1.6nm and that more than 50% of these SWCNTs were observed with filling. All of the nanotubes observed with filling within this diameter range were found to correspond to the novel tubular form of HgTe.…”
mentioning
confidence: 99%
“…15 The samples were then fully characterised using HRTEM to ensure that no extraneous HgTe remained and determine the atomic structure of the filling structures. 15,16 Inspection of more than 100 SWCNTs from the supplied sample by HRTEM revealed that the significant majority (~85%) fall within a limited diameter range of 1.2-1.6nm and that more than 50% of these SWCNTs were observed with filling. All of the nanotubes observed with filling within this diameter range were found to correspond to the novel tubular form of HgTe.…”
mentioning
confidence: 99%
“…The images throughout Figure 1A-F, depict low dimensional, confined HgTe extreme nanowires, with a diameter of ~1 nm, whose microstructure corresponds to the form discussed in ref 14 . Representative images of bundles and discrete tubes are presented in Figure 1D.…”
Section: Representative Resultsmentioning
confidence: 56%
“…The final key indicator that specific Raman features are associated with nanowires rather than nanoparticles or lumps of the parent material is a characteristic polarization dependence like that shown in Figure 3. As discussed in more detail in reference 14 the Raman scattering from an ensemble of randomly oriented 1D systems is preferentially polarized in the same direction as the exciting laser light with a contrast ratio of 3:1 and thus shows the characteristic figure of eight shape present in the optimum results shown in Figure 3. It is important to test that preferred emission direction rotates with the excitation polarization, as shown in Figure 3, as polarized Raman due to other mechanisms is not uncommon.…”
Section: Representative Resultsmentioning
confidence: 91%
See 2 more Smart Citations